JENIS PUKULAN YANG BANYAK MENGHASILKAN POIN PADA PERMAINAN TENIS MEJA - Hamid, Abd. (Vidya Karya Jurnal Kependidikan, 2013)
This research has the objective to know the technique of beating commonly creating the point in table tennis game to players of table tennis game organization Hippindo and to know the result of beating commonly producing point by competing in half competition. It is found that the technique commonly creating the point in table tennis game is top spin, smash, back spin, drive, left side spin, chop, push, dropshot, block, right side spin, top spin, back spin, and flick.